3 in 1 soil sensor / Baity Nuredreen Ismail … [et al.] - Ismail, Baity Nuredreen; Alias, Masliza; Zakaria, Nur Syahira; Md Ali, Nur Syuhadah; Muhamad Hanapiyah, Zulkefli (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
3 in 1 Soil Sensor will monitor soil pH, nutrient levels and moisture. The main objective of this product is to make it easier for gardeners, farmers, and agricultural workers to manage the condition of their soil in order to produce better crops. Farmers will no longer need to use multiple products to monitor soil pH, nutrient levels, or soil moisture levels. A solar panel with its own function allows the device to run completely without the usage of batteries or other energy sources. The 3 in 1 Soil Sensor was designed to monitor soil conditions for gardeners, farmers and agricultural employees. It has a digital display which makes it easier for users to read soil measurements. 3 in 1 Soil Sensor can monitor three main functions at once. This means farmers will only need to spend 15 minutes a day on their crops, which will save them time and energy. Agriculture requires an innovative tool because the crop is an important thing that must be treated for in order to create a high-quality crop. Gardening tools, such as 3 in 1 Sensors, provide a proper soil measuring system to simplify soil management of crops.